Developing Self-Assessment Instruments to Measure The Pedagogical Competence of Prospective Teacher Students - Setiawati, Esti; Yassin, Abdulnassir; Marzuki, Sharifah Zannierah Syed; Chen, Zhang; Novianto, Victor (International Journal of Social Learning (IJSL), 2024)
This research aims to develop a self-assessment of the pedagogical competence of prospective teacher students in the school field introduction program. The research method used is research and development with the Plomp model, which consists of five stages: initial investigation, product design, realization/construction, testing, evaluation and revision, and implementation. The sample was determined purposively, totaling 58 students. At the testing stage, experts judge the instruments based on the Content Validity Index. The instrument measured instrument's reliability was measured, and data collected from student teachers was analyzed using descriptive statistical methods. The research results show 1) The Content Validity Index content of the self-assessment instrument is 0.91, which is in the almost perfect category; 2) The reliability inmost more than 0.70, which 2 means it meets the recommended criteria; 3) The Self-assessment showed that 87.08% of study; 3 mastered pedagogic compe which consisted of five aspects.